Proyecto de factibilidad para la creación de una comercializadora de textiles en el cantón General Villamil Playas para su venta al menudeo - Vinces Cerezo, Sidney (2010)
General Villamil Playas hasn´t a local textile fabrics, has great variety and good quality. People should move to others cities so Guayaquil or Libertad to shop, these are the closest in the canton. By implementing this project we have in mind mainly the woman, she is owns the home. It is responsible for the decoration of yours home, caring for your family to be spotless and well light. Therefore we want to offer a room with the widest variety of fabrics and excellent quality for making clothing, linens and curtains. That's the reason of this study; the project aims to measure the feasibility of implementing trading textiles for the manufacture of clothing, sheets and curtains, in the widest variety and excellent quality in Canton General Villamil Playas. Assess the economic and social desirability of implementing a trading through a market survey to identify the decision variables in terms of customer preferences, to develop a business plan for the sale of textiles, will be our goal principal and a marketing plan that shows THE BIGEST FABRICS, FOR ALL TYPES OF CUSTOMERS in order to meet the needs of our consumers by providing a national product quality.